Effect of Exposure to Famine during Early Life on Risk of Metabolic Syndrome in Adulthood: A Meta-Analysis - Lu-Lu Qin; Bang-An Luo; Fan Gao; Xiang-Lin Feng; Jia-He Liu (Journal of Diabetes Research)
Background. Emerging studies have explored the association between the famine exposure during early life and the risk of the metabolic syndrome, and the results remain controversial. This meta-analysis was performed to summarize the famine effects on the prevalence of metabolic syndrome (MetS) in adulthood. Materials and Methods. We searched the PubMed, Web of Science, Embase, ScienceDirect, and Chinese National Knowledge Infrastructure for relevant studies up to December 2019. Pooled odd ratios (ORs) with 95% confidence intervals (CIs) were used to estimate the effect exposure to famine on MetS using a random-effects model, and the I2 was used to evaluate the heterogeneity. Results. The analyses included 39 studies from 10 articles with a total of 81504 participants. Fourteen studies from 10 articles for fetal famine exposure, 20 studies from 7 articles for childhood famine exposure, and 5 studies from 3 articles for adolescence/adult famine exposure were included in this meta-analysis. Compared with a nonexposed group, famine exposure significantly increased the risk of MetS for early life famine exposure (OR=1.27, 95% CI: 1.18-1.38), fetal famine exposure (OR=1.27, 95% CI: 1.14-1.43), and childhood famine exposure (OR=1.29, 95% CI: 1.16-1.44). Subgroup analyses showed that the result was consistent regardless of the study designs, definitions of MetS, and causes of famine, with or without adjustment for age, smoking, drinking, and physical activity. Conclusions. This meta-analysis suggests that exposure to famine during early life may increase the risk of MetS in adulthood.